Regeneration Status and Soil Nutrient Content in Burned Blue Pine Forest in Thimphu, Western Bhutan - Namgay Shacha; Yonten Dorji; Arjun Nepal; Sangay Choden; Tez Bdr Ghally; Karma Chorten Dendup (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
A forest fire and human disturbances are a major threat to regeneration and forest health. This study was conducted in western Bhutan in Thimphu, above Depsi. The Objective of the research was to assess diversity, species richness, regeneration, and soil nutrients content (N, P& K) along the altitudinal gradient after a forest fire. A total of 30 standard plots of size 20x20 m plots were established in the burned blue pine forest systematically, along the altitudinal gradient. Systematic random sampling was adopted. Sampling was carried out at three different altitudinal zones that is; lower (2500-2700 masl), middle (2701-2900 masl), and higher (2901-3100 masl) altitude. A total of 1703 individual plants belonging to 21 families were recorded from the study area. The diversity, regeneration, and soil nutrient increased till mid-altitude and decreased with further increase in altitude, making a unimodal, hump shape pattern. The regeneration, soil nutrient, and diversity were higher in the gentle slope and the slope facing southeast due to the longer duration of sunlight exposition. The regeneration and diversity of vegetation showed a positive correlation with aspect, carbon, phosphorous, and nitrogen (p<.05). The diversity and regeneration after a fire was affected by environmental factors, especially soil nutrients, aspect, and slope. The study forms the baseline data for the forest manager to sustainably restore the forest after a fire.  Species resistant to fire can be chosen for forest restoration. It can also be incorporated in management plans for sustainable management and conservation of mountain blue pine forests.